Intermittent pneumatic compression therapy as a preventive measure for venous thromboembolism after total hip arthroplasty: A systematic review - Vishal Singh; Arushi Mishra; Deeksha Sharma; Umang Singal; Najeeb Islam; Mohammad Jahirul Islam; Md. Amran Hossain; Md Saifur Rahman; Sohel Ahmed (PLoS ONE, 2025)
Background Venous thromboembolism (VTE) is a significant and avoidable complication that may occur after total hip arthroplasty (THA). Various mechanical and chemical prophylactic measures may mitigate this elevated risk of death and functional impairment. Consequently, early prevention of VTE is essential via the identification of related risk factors. Methods A search was performed using the databases of PubMed, ScienceDirect, PEDro, and Cochrane Library to get papers from 2004 to 2024 in accordance with PRISMA guidelines. Only randomized controlled trials (RCTs) published in English that included at least one group undergoing intermittent pneumatic compression (IPC) treatment as a prophylactic intervention after total hip arthroplasty (THA) were included. This systematic review has been registered in PROSPERO. The quality evaluation of the included studies was conducted using the PEDro scale and the Cochrane risk of bias instrument. Result We selected 12 studies from a total of 733 based on predetermined criteria. A total of 2,352 patients of both genders underwent total hip arthroplasty, comprising 1,294 patients in the experimental group and 1,058 patients in the control group across the included studies. The results indicate that the combination of IPC and pharmaceutical agents was the most effective treatment for reducing VTE risk in patients who underwent THA. Conclusion IPC therapy is very effective in avoiding VTE, particularly when used in combination with pharmacological therapies after THA surgery. The best ways to lower the risk of VTE are to use both IPC and anticoagulants together. However, IPC alone may lower the risk of VTE compared to not using any prevention at all. In general, IPC is a crucial component of comprehensive VTE prevention strategies in THA.